M23 The use of Wearables for COPD patients: A Qualitative study. (12th November 2015) - Nabhani, S; Siva, R; Kayyali, R; Yagambrun, C; Robinson, P; Spruit, M; Vaes, A; Wacker, J; Caldani, L; Paradiso, R; Chang, J
Abstract : There have been significant advances in Technology enabled care (TEC) including wearable technology. However, to our knowledge, there is a paucity of literature related to patient perceptions of smart wearable sensors. The WELCOME platform (FP-7 funded project) is an innovative integrated system using wearable sensors and smart computing for COPD patients with co-morbidities. 1 The aim of this platform is the early diagnosis of exacerbations and disease deterioration allowing for early intervention. The wearable sensors in this project have been integrated into a vest (Figure 1 ) and several prototypes with mock sensors were developed. A structured interview was designed to explore COPD patient perceptions pertaining to vest comfort, ease of wear and handling, willingness to use and concerns. Interviews were designed to take place at the clinic (England and Netherlands) where patients are provided with a suitably sized vest to try on followed by the structured interviews. To date, 15 interviews have been completed at Croydon Healthcare services Trust, and the Dutch interviews are underway. Results: The interview transcripts were thematically analysed using mostly framework analysis. Analysis was conducted using NVIVO 10. The following themes emerged from the data.1) Acceptance of vest 2) willingness to wear the vest during daytime 3) Discomfort with sensor size and shape prohibiting night wear 4) Demonstrated capability of donning the vest and handling of the sensors 5) Safety concerns emphasising importance of patient education before use 6) Gender related concerns regarding vest design. Conclusion: The vests were well received by patients however the above results illustrate the importance of involving the end users in the design and development of any smart intervention. These results will be used for the final design and development of the vest. Reference: 1 Chouvarda I, Philip NY, Natsiavas P, et al . WELCOME-innovative integrated care platform using wearable sensing and smart cloud computing for COPD patients for comorbidities. Conf Proc IEEE Eng Med Biol Soc . 2014;2014 :3180–3. doi: 10.1109/EMBC.2014.6944298